2017
DOI: 10.3892/mco.2017.1263
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of aggressive treatment in esophageal cancer patients with synchronous solitary brain metastasis

Abstract: Abstract. The aim of the present study was to investigate the outcomes of esophageal cancer (EC) patients with isolated synchronous brain oligometastasis (oligo-BM) treated with chemoradiotherapy (CRT) of the primary site and localized treatment of the BM with surgery, radiotherapy (RT) or radiosurgery. Of 125 EC patients investigated, seven patients (6%) had solitary BM. Six patients were diagnosed prior to, and one patient was diagnosed during, treatment. All patients were treated with neoadjuvant chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…All but one patient received definitive chemoradiothearapy and whole-brain radiotherapy. The median survival time was 18.9 months (range: 10.0-27.2 months) 12 . Welch G et al found that for esophageal cancer patients with brain metastasis, OS was superior for those initially had surgical resection with the 1-year OS as high as 67% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…All but one patient received definitive chemoradiothearapy and whole-brain radiotherapy. The median survival time was 18.9 months (range: 10.0-27.2 months) 12 . Welch G et al found that for esophageal cancer patients with brain metastasis, OS was superior for those initially had surgical resection with the 1-year OS as high as 67% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Additional small series, including Hiyoshi et al and Huddy et al, demonstrated similar findings [43,47]. Onal et al's investigation of outcomes in esophageal cancer patients with isolated synchronous brain oligometastasis included five patients with adenocarcinoma out of the seven included for analysis [48]. Patients underwent definitive chemoradiotherapy of the primary tumor and locally ablative treatment of the brain metastasis, with a median time to progression of 8 months and median survival of 18.9 months.…”
Section: Evidence For Management Of Oligometastasismentioning
confidence: 81%
“…Two studies assessed survival in oesophageal cancer patients presenting with synchronous oligometastasis[36,37] (Supplementary Tables 4 and 5). Onal et al[36] assessed the impact of an aggressive treatment approach of both primary tumour and solitary brain metastasis. Patients underwent definitive CRT of the primary tumour locally ablative treatment of the brain metastasis, consisting of radiotherapy, surgery or radiosurgery.…”
Section: Resultsmentioning
confidence: 99%
“…Hiyoshi et al[34] did not show any benefit in the resection of lesions in the brain or bone. In contrast with this, Onal et al[36] suggested an improvement in survival outcome in patients with oligometastatic brain metastasis when treated with an aggressive approach of both the primary tumour and the metastatic lesion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation